Climate change and disease dynamics: Predicted changes in ecological niches for Rift Valley fever in East Africa - Bett, Bernard K.; Otieno, Fredrick T.; Murithi, Faith (Elsevier, 2019)
Climate change has precipitated tremendous changes in the spatial distribution of multiple infectious diseases, particularly those transmitted by arthropod vectors. In this paper, we investigate the effects of global warming on the distribution of Rift Valley fever (RVF) in East Africa based on the 2050 climate change projections from the global climate model (CCSM4). Two of the four representative concentration pathways (RCPs) - RCP 4.5 and RCP 8.5 - are used to cover alternative projections of the radiative forcing levels. Ecological niche modelling, implemented using the Random Forest algorithm, is used for these scenario analyses. Generally, global warming is predicted to cause local shifts on ecological niches of RVF, with some of the infected areas such as those in the coastal Kenya and northern Tanzania being expected to become more suitable for the disease. This indicates the need for an improvement in the delivery of the existing RVF control measures as well as the development of more effective control technologies to better manage the current and future RVF risks.